Shaofu Zhuyu decoction for primary dysmenorrhea: A protocol for systematic review and meta-analysis. Issue 23 (11th June 2021) - Yuan, Lei; Lin, Dan; Kang, XueLiang; Ye, Yu
Abstract: Background: Primary dysmenorrhea (PD), one of the common gynecological diseases, is more common in adolescent women. According to epidemiological investigation, the incidence of PD accounts for about 60% of all patients with dysmenorrhea, and its symptoms seriously affect the normal working life of women, so it is important to find a more safe and effective treatment. In recent years, traditional Chinese medicine has made a lot of achievements in the treatment of female PD, among which a number of clinical studies have shown that Shaofu Zhuyu decoction (SFZY) can significantly improve the symptoms of dysmenorrhea and improve the therapeutic effect. Therefore, we intend to conduct a systematic review to further clarify the efficacy and safety of SFZY in the treatment of PD. Methods: We will search each database from the built-in until May 2021. The English literature mainly searches Cochrane Library, PubMed, excerpt medica database, and Web of Science, while the Chinese literature comes from China National Knowledge Infrastructure, Chinese biomedical literature database, VIP, and Wanfang database. Simultaneously we will retrieval clinical registration tests and grey literatures. This study only screen the clinical randomized controlled trials about XFZY for PD to assess its efficacy and safety. The 2 researchers worked independently on literature selection, data extraction, and quality assessment. The dichotomous data is represented by relative risk, and the continuous is expressed by mean difference (MD) or standard mean difference, eventually the data is synthesized using a fixed effect model or a random effect model depending on whether or not heterogeneity exists. The clinical efficacy and the score of dysmenorrhea symptoms were evaluated as the main outcomes. The artery pulsatility index (API), resistance index (RI), peak systolic/diastolic peak (S/D) were secondary outcomes. Finally, meta-analysis was conducted by RevMan software version 5.3. Results: This study will provide high-quality evidence for treatment of PD with SFZY in terms of effectiveness and safety. Conclusion: This systematic review aims to provide new options for SFZY treatment of PD in terms of its efficacy and safety. Ethics and dissemination: This study does not require ethical approval. We will disseminate our findings by publishing results in a peer-reviewed journal. OSF registration number: DOI: 10.17605/OSF.IO/DXZHR.